(untitled) (Journal of actual problems of jurisprudence, 2019)
The article analyzes the provisions of the Criminal Code of the Republic of Kazakhstan in 2014, which governing the plurality of criminal offenses. The study forms a plurality of criminal offenses and their legal consequences allowed to the authors to identify the main trends in the development of the institution plurality of criminal offenses and theoretically justify legislative innovations of recent years. Key words: multiplicity of criminal offences, repeated of criminal offences, totality of criminal offences, relapse of crimes.